2018
DOI: 10.1038/d41586-018-05719-4
|View full text |Cite
|
Sign up to set email alerts
|

The amyloid hypothesis on trial

Abstract: I n early 2018, two high-profile clinical trials of drugs for Alzheimer's disease ended in disappointment. The drugs joined a long list of potential treatments that have failed to deliver significant benefits in people. Their development was guided by an idea that has dominated research on Alzheimer's disease for more than 25 years: the amyloid hypothesis, which is the assumption that accumulation of the peptide amyloid-β is the main cause of the condition. Researchers proposed that when amyloid-β clumps toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
253
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(269 citation statements)
references
References 14 publications
3
253
0
13
Order By: Relevance
“…The advent of these new technologies allows tackling in a novel way a central question in AD research, i.e., what is the relationship of amyloid plaques to the neurodegenerative process in brain? The question is particularly relevant given the emerging insight and worry that amyloid lowering therapies show little efficacy with regard to memory improvement (Gallardo and Holtzman, 2017;Makin, 2018). Some investigators have suggested that the plaques are inert and that soluble oligomeric Aβ drives neurotoxicity (Glabe, 2008;Ono, Condron and Teplow, 2009;Mucke and Selkoe, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of these new technologies allows tackling in a novel way a central question in AD research, i.e., what is the relationship of amyloid plaques to the neurodegenerative process in brain? The question is particularly relevant given the emerging insight and worry that amyloid lowering therapies show little efficacy with regard to memory improvement (Gallardo and Holtzman, 2017;Makin, 2018). Some investigators have suggested that the plaques are inert and that soluble oligomeric Aβ drives neurotoxicity (Glabe, 2008;Ono, Condron and Teplow, 2009;Mucke and Selkoe, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tatsächlich werden solche Einwände derzeit intensiv diskutiert. [60] Andererseits gibt es überwältigende Evidenz für eine Schlüsselrolle des Amyloidbildungsprozesses bei der Pathogenese relevanter Krankheiten. [4] Die Fehlschläge in den klinischen Studien kçnnten daher auch darauf hinweisen, dass die Kandidatenmoleküle ihre Zielstrukturen nicht früh genug oder effektiv erreichen konnten.…”
Section: Zusammenfassung Und Ausblickunclassified
“…As a result, considerable resources have been expended over the past forty years in searching for therapeutics to treat AD, all of which have failed—sometimes repeatedly—in late‐stage clinical trials (Khachaturian, ; Martin, ; Morris, Clark, & Vissel, ; Mullane & Williams, ; Panza et al., ). Among the reasons for these failures are: (i)The politicization of AD, which has tended to confuse the guidelines for the diagnosis and treatment of a disease that is increasingly viewed as multifactorial and non‐linear in both causality and progression (De Strooper & Karran, ; Medina, Khachaturian, Rossor, Avila, & Cedazo‐Minguez, ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, considerable resources have been expended over the past forty years in searching for therapeutics to treat AD, all of which have failed-sometimes repeatedly-in late-stage clinical trials (Khachaturian, 2018;Martin, 2018;Morris, Clark, & Vissel, 2018;Mullane & Williams, 2018a;Panza et al, 2019). Among the reasons for these failures are:…”
Section: Introductionmentioning
confidence: 99%